DIGITAL INTERMEDIATION, INTERNET USAGE AND THE DEVELOPMENT OF COGNITIVE STYLES - Šņitņikovs, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Application of information and communication technologies in education has changed not only the forms of organization of educational process but also the way students learn. Studies over the last decade have shown that availability of the internet has changed the way students search, perceive, remember and assimilate new information and knowledge. This paper uses the works of cultural-historical psychology, media studies and cognitive psychology to ground the idea that the use of the media affects the development of cognitive styles. Computer technologies are conceptualized as cultural means, as psychological tools and new forms of intermediation between the consciousness and productive activity. As such, computer technologies and specifically the internet have the potential of influencing the development of higher psychic functions, the forms of cognitive self-control and self-government. The paper discusses the application of Sternberg’s conception of thinking styles to the problems of the influence of computer technologies on the development of styles of cognitive self-control. As empirical evidence the paper uses the materials of five focus group discussions with school and university teachers conducted within the project “The impact of internet usage patterns on the development of youth’s cognitive styles”.